Drifting algal mats as an alternative habitat for benthic invertebrates: Species specific responses to a transient resource - Norkko, J.; Bonsdorff, E.; Norkko, A. (Journal of Experimental Marine Biology and Ecology, 2000)
Patchy occurrences of benthic drift algae (i.e. loose lying macroalgal mats) may increase habitat complexity on normally bare soft bottoms, but at the same time, extensive amounts of drifting algal mats are known to stress the benthic fauna. This paper presents results of the first detailed study of the fauna associated with drift algal mats in the northern Baltic Sea. In order to assess the importance of drifting algae as an alternative habitat for benthic fauna, benthic drift algal mats were sampled on shallow (2-9 m) sandy soft bottoms in the outer archipelago of the Aland Islands (Finland). Species composition, abundance and biomass of the macrofauna associated with algal mats were recorded. The results show that drifting algae at times can harbour very high abundances of invertebrates (up to 1116 individuals/g algal dryweight), surpassing invertebrate densities recorded in seagrass communities. The algal fauna varied between sites and over time, and factors such as ambient benthic fauna, exposure to wind-wave disturbance, depth, and algal coverage and condition influenced the invertebrate community composition of the algal mats. Abundance increased while individual biomass of the animals decreased over time (summer season; July-October). A series of laboratory experiments were conducted in order to test the ability of a few important benthic species to move up into, and survive in a drifting algal mat. Macoma balthica, Hydrobia spp., Nereis diversicolor and Bathyporeia pilosa were used in the experiments, and significant differences in their survival and mobility within drifting algae were recorded. This study shows that benthic species differ significantly in their ability to utilise the algal mats, with mainly opportunistic and mobile taxa such as Hydrobia spp., Chironomidae and Ostracoda benefiting from the algae, whereas infaunal species such as M. balthica and B. pilosa are negatively affected. The occurrence of eutrophication induced drifting macroalgal mats has increased significantly during the last decade in the northern Baltic Sea. Hence, the importance of drifting algae as a stress factor and as an alternative habitat for benthic fauna increases
NeMys doc_id: 11185